Analysis of intention to purchase travel on the Web - German Gemar; Ismael P. Soler; Laura Melendez (Tourism & Management Studies)
The Internet’s role in global market development merits more extensive research, which is especially true for Spain’s tourism industry because of its contribution to the national economy. The Web’s intangible nature also makes it the most effective distribution channel. To help companies differentiate their websites, this study tested a model of purchase intention that includes its determinants. Cluster analysis of a representative sample was conducted to sort potential and current consumers of online travel services into groups based on their perceptions of the model’s factors. While young consumers see purchasing tourismrelated services on the Internet as easy and cost-effective, the opposite results were obtained for the elderly. However, the perceived risks are considered important by most individuals. To maximise the benefits of e-commerce, companies must develop strategies that meet each type of client’s expectations